Escalation, maintenance and abstention in oncology a new study design to identify how individual values of patients impact on the assessment of risks and benefits of novel therapeutic concepts in cases of gynaecological tumors and colorectal cancer: a study protocol - Susanne Theis; Jülide Senyigit; Britta Büchler; Gesa Kolck; Markus Moehler; Annette Hasenburg; Norbert Paul (Frontiers in Oncology)
Being diagnosed with cancer is a life-altering event that profoundly reshapes an indivdual’s biography, especially in terms of temporality and physicality. Modern treatment approaches, such as maintenance therapy or therapeutic abstinence, often conflict with patients’ desire for a radical fight against the disease. Decision-making about therapeutic goals is shaped by the tension between medical-scientific expertise and personal values and experiences, making it particularly challenging to align diverse preferences and norms. This study aims to analyse values in the context of the challenging human experience of cancer. We hypothesise that conventional quantitative measures, including patient-reported outcome measures (PROMs) may be insufficient to fully capture patients’ perspective on therapeutic success. To address this, we will conduct semi-structured interviews with individuals diagnosed with gynecological or colorectal cancer. Using a mixed methods approach, we aim to identify patients’ values, treatment goals, and expectations. The study’s key outcomes include: 1) an ethical analysis of values in the context of cancer experiences 2) a reconstruction of values that shape individual treatment goals and expectations and 3) a comparison between ethical concepts of successful life, patients’ situational values, and evidence-based medical preferences. Building on these insights, the study pursues three secondary objectives: 1) developing a strategy for patient-centred adaptation of clinical evaluations of treatment approaches, including escalation, maintenance and abstinence, 2) designing a well-defined clinical framework for therapeutic goal setting, and 3) integrating this framework into medical education, addressing clinical, oncological, ethical and communication competencies.